2017
DOI: 10.1111/echo.13533
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial function and phenotypes in asymmetric hypertrophic cardiomyopathy

Abstract: LA function was impaired in patients with HCM even in minimally symptomatic nonobstructive phenotype. Total and passive LA function was further impaired in patients with obstructive HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…However, some researchers showed that contractile function of LA was relatively preserved while reservoir and conduit function were significantly impaired among HCMP patients as measured by LA strain, 22) 23) 29) results of patients with different ages, heart function, and analyzing systems. Kobayashi et al 29) calculated LA strain with LA wall length and presented impaired total and passive LA function in obstructive HCMP. Other studies showed preserved contractile function using XStrain software (Esaote S.p.A, Florence, Italy).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers showed that contractile function of LA was relatively preserved while reservoir and conduit function were significantly impaired among HCMP patients as measured by LA strain, 22) 23) 29) results of patients with different ages, heart function, and analyzing systems. Kobayashi et al 29) calculated LA strain with LA wall length and presented impaired total and passive LA function in obstructive HCMP. Other studies showed preserved contractile function using XStrain software (Esaote S.p.A, Florence, Italy).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that LAV was significantly higher than that of the control group ( P < 0.05). Although HCM patients in this study had no obvious clinical symptoms, LA function was also impaired in HCM patients with no symptoms or mild symptoms [ 24 ]. Moreover, we found that LAV was significantly correlated with GCW, GWW and GWE, considering that patients with HCM had both systolic and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the view on the LA booster pump function is still divided in the existing literature. Yukari et al [22] demonstrated that all phasic LA functions containing booster pump function significantly declined in patients with HCM compared with the healthy group. Other researchers considered LA booster pump function as a compensatory mechanism for the LVEF via enhancing LAAEF and contraction strain; in their study, HCM patients had lower reservoir and conduit function while having enhanced pump function in comparison with the control group [23, 24].…”
Section: Discussionmentioning
confidence: 99%